Modalidades de la escritura ficcional de la sacralidad monárquica (Castilla-León, siglo XIII) - Amaia Arizaleta (Les Cahiers de Framespa)
This article aims to study the representations of the sinful monarch, that is ultimately redeamed. Two texts emanating from the Castilian-Leonese thirteenth century context will serve as a basis for this paper, and as exemples of the twofold clerical construction of monarchy: Libro de Alexandre and Libro de Apolonio. In these texts it is possible that propaganda issues are not brought to the fore, rather it might be suggested that the ruler needed the clerics present in court circles.